Sanksi Pidana terhadap Pemberi Kerja dalam Undang- undang No.11 Tahun 2020 tentang Cipta Kerja - Kalingga Maulana Ibrahim; Nyoman Sugiartha; I Putu Gede Seputra (Warmadewa Press, 2022)
Job Creation Law is a new law that is attracting controversy, especially among workers. The problem that can be raised in this is how to regulate the law and the law sanctions contained in this Job Creation law. The type of research used in this report uses the type of normative legal research with a statutory and conceptual approach. Collection of legal materials uses secondary legal materials collection. While the analysis used is a qualitative analysis. So that the result of this report can find how the legal arrangements and sanctions contain it because this Job Creation Law has changed the rules that are considered good in previous Laws such as regarding Minimum Wages, Outsourcing, Certain Time Work Agreement, Severance Pay and act.